Anti‐inflammatory effects of ADAMTS‐4 in a mouse model of ischemic stroke. Issue 9 (15th June 2016) - Lemarchant, Sighild; Dunghana, Hiramani; Pomeshchik, Yuriy; Leinonen, Henri; Kolosowska, Natalia; Korhonen, Paula; Kanninen, Katja M.; García‐Berrocoso, Teresa; Montaner, Joan; Malm, Tarja; Koistinaho, Jari
Abstract : ADAMTS‐4 (a disintegrin and metalloproteinase with thrombospondin motifs type 4) is a metalloprotease capable to degrade chondroitin sulfate proteoglycans leading to cartilage destruction during arthritis or to neuroplasticity during spinal cord injury (SCI). Although ADAMTS‐4 is an inflammatory‐regulated enzyme, its role during inflammation has never been investigated. The aim of this study was to investigate the role of ADAMTS‐4 in neuroinflammation. First, we evidenced an increase of ADAMTS‐4 expression in the ischemic brain hemisphere of mouse and human patients suffering from ischemic stroke. Then, we described that ADAMTS‐4 has predominantly an anti‐inflammatory effect in the CNS. Treatment of primary microglia or astrocyte cultures with low doses of a human recombinant ADAMTS‐4 prior to LPS exposure decreased NO production and the synthesis/release of pro‐inflammatory cytokines including NOS2, CCL2, TNF‐α, IL‐1β and MMP‐9. Accordingly, when cell cultures were transfected with silencing siRNA targeting ADAMTS‐4 prior to LPS exposure, the production of NO and the synthesis/release of pro‐inflammatory cytokines were increased. Finally, the feasibility of ADAMTS‐4 to modulate neuroinflammation was investigated in vivo after permanent middle cerebral artery occlusion in mice. Although ADAMTS‐4 treatment did not influence the lesion volume, it decreased astrogliosis and macrophage infiltration, and increased the number of microglia expressing arginase‐1, a marker of alternatively activated cells with inflammation inhibiting functions. Additionally, ADAMTS‐4 increased the production of IL‐10 and IL‐6 in the peri‐ischemic area. By having anti‐inflammatory and neuroregenerative roles, ADAMTS‐4 may represent an interesting target to treat acute CNS injuries, such as ischemic stroke, SCI or traumatic brain injury. GLIA 2016;64:1492–1507 Main Points: Parenchymal ADAMTS‐4 expression is increased during ischemic stroke in mice and in humans. ADAMTS‐4 has an anti‐inflammatory effect in vitro in microglia and astrocyte cultures, and in vivo after ischemic stroke.